2020
DOI: 10.1017/s0022377820000732
|View full text |Cite
|
Sign up to set email alerts
|

Island divertor configuration design for a quasi-axisymmetric stellarator CFQS

Abstract: A magnetic field configuration of an island divertor for a quasi-axisymmetric stellarator (CFQS) is proposed. The configuration incorporates large islands surrounding the core confinement region. The interface between the core region and the peripheral region of the island divertor is a clear magnetic separatrix similar to a tokamak divertor. The structure of divertor magnetic field lines is very regular without stochasticity and the connection length is sufficiently long for good divertor performance. Such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It has been proposed that, to reduce the deformation of the magnetic flux surfaces in the CFQS, in addition to 16 modular coils, external auxiliary coils with appropriate currents should be employed in high β cases [19]. Recently, Kinoshita et al reported the additional coil systems of the CFQS, including poloidal field coils to control the plasma position and shape and toroidal field coils to control the iota profile [19], which support a possible way to achieve an island divertor configuration for the CFQS [26].…”
Section: Calculations Of the Cfqs Equilibriummentioning
confidence: 99%
“…It has been proposed that, to reduce the deformation of the magnetic flux surfaces in the CFQS, in addition to 16 modular coils, external auxiliary coils with appropriate currents should be employed in high β cases [19]. Recently, Kinoshita et al reported the additional coil systems of the CFQS, including poloidal field coils to control the plasma position and shape and toroidal field coils to control the iota profile [19], which support a possible way to achieve an island divertor configuration for the CFQS [26].…”
Section: Calculations Of the Cfqs Equilibriummentioning
confidence: 99%
“…10. This configuration has been designed by S. Okamura, et.al [51]. The confinement region is bounded by an island bundle with ι=2/5, which determines the last closed flux surface (LCFS).…”
Section: (D)-(f)mentioning
confidence: 99%
“…In addition to the standard quasi-axisymmetric configuration shown in figure 1, the island bundle divertor (IBD) configuration can be also achieved without breaking the quasiaxisymmetry in the core confinement region by adding a weak toroidal field to the quasi-axisymmetry, displayed in figure 10. This configuration has been designed by S. Okamura, et al [49]. The confinement region is bounded by an island bundle with ι = 2/5, which determines the last closed flux surface (LCFS).…”
Section: Configuration Preparties In Fixed and Free-boundary Equilibriamentioning
confidence: 99%
“…An equilibrium with 2/4 magnetic islands was found in the simulation results with the HINT code [10]. 12 planar TFC have been designed to adjust the rotational transform profile [54], healing magnetic islands. Moreover, active control of islands is also available by electron cyclotron heating and tailoring the pressure profile [55,56].…”
Section: Effects Of Bootstrap Current On Neoclassical Transport and Jmentioning
confidence: 99%